2019
DOI: 10.3390/ijerph16244886
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction in the Spanish National Health Service: Partial Least Squares Structural Equation Modeling

Abstract: The aim of this article was to determine which key indicators influence patient satisfaction with the Spanish NHS to provide useful information for policy decision-making. A total of 33 variables for each of the 17 Spanish autonomous communities were collected from the statistical portal of the Spanish Ministry of Health, Social Services, and Equality between 2005 and 2016. A cross-sectional study was applied using Partial Least Squares to a Structural Equation Model (PLS-SEM). The influence of expenditures, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 69 publications
3
28
1
1
Order By: Relevance
“…In line with previous literature, we found that men and women value family and specialist doctors more than the health system as a whole [ 53 , 68 , 69 ]. In contrast, women are more satisfied with family doctors and men with specialist doctors.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In line with previous literature, we found that men and women value family and specialist doctors more than the health system as a whole [ 53 , 68 , 69 ]. In contrast, women are more satisfied with family doctors and men with specialist doctors.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies confirm the logical assertion that the volume of available resources directly affects the level of use of health services. It stands to reason that, if users have more resources at their disposal, they will use the system more frequently [ 53 ]. Therefore, we propose the next hypotheses:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the satisfaction with the Spanish national health service was 57.1%. 31 In Ethiopia, the satisfaction was 60.7% among adolescents aged 15 to 17 years. 32 As for the elderly aged 65 years or above, the satisfaction was 71% in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Structural equation modeling (SEM) is a statistical modeling technique to describe relationships between theoretical constructs, represented by regression or path coefficients between the factors [12]. SEM could become an indispensable tool for managers, policymakers, and regulators in the healthcare sector [13]. It implies a structure for the covariance between the observed variables, and latent factors.…”
Section: Structural Equation Modelingmentioning
confidence: 99%